Inovasi dalam Desain Grafis dan Visualisasi - Paramita Hapsari, S.Ds, M.Ds, Paramita Hapsari, S.Ds, M.Ds (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2024)
This research investigates the latest trends in graphic design and visualization and their impact in visual communication. Through literature analysis and case studies, the study identifies key innovations in graphicdesign and visualization that influence the way messages are delivered and received by audiences. Freshness in visual communication can increase the appeal of products and brands. This research investigates the latest trends in graphic design and visualization and their impact in visual communication. Through literature analysis and case studies, the study identifies key innovations in graphic design and visualization that influence the way messages are delivered and received by audiences. Qualitative research methods are used to analyse how technology, culture, and market needs have shaped the latest developments in graphic design and visualization. In the generative design approach, graphic design not only creates an attractive visual aesthetic, but also reflects the company's values and vision. This leads to the question of how this approach affects consumer perception, advantages and challenges in its implementation, as well as comparisons with conventional designs. The results showed that generative design can: 1). Enhances the innovative, modern, and creative impression of the brand, attracting consumers who are looking for something different. 2). Involve consumers in the design process, strengthen brand-consumer relationships and create more personalized experiences. 3). Communicate the company's values in a unique and attractive way, differentiating the brand from competitors. However, challenges such as the development of proper algorithms and the maintenance of brand consistency remain in focus. Consumer perceptions of generative design are usually perceived as more innovative and creative, while conventional designs tend to feel more tied to existing norms.